2006
DOI: 10.1111/j.1471-4159.2006.04162.x
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages are comprised of resident brain microglia not infiltrating peripheral monocytes acutely after neonatal stroke

Abstract: Macrophages can be both beneficial and detrimental after CNS injury. We previously showed rapid accumulation of macrophages in injured immature brain acutely after ischemia-reperfusion. To determine whether these macrophages are microglia or invading monocytes, we subjected post-natal day 7 (P7) rats to transient 3 h middle cerebral artery (MCA) occlusion and used flow cytometry at 24 and 48 h postreperfusion to distinguish invading monocytes (CD45high/ CD11b+) from microglia (CD45low/medium/CD11b+). Inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
129
2
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(149 citation statements)
references
References 77 publications
17
129
2
1
Order By: Relevance
“…Moreover, we showed that blood‐derived macrophages began infiltrating the hippocampus in the P9 pups 1 day after HI, but few blood‐derived macrophages infiltrated the hippocampus of the 3mo mice at the same time point. Denker et al reported that the population of blood‐derived macrophages (CD45 high macrophages) in the injured hemisphere 24 hours after HI of P7 rats was 8.8 ± 6.7% and the majority of macrophages were resident microglia (CD45 low and CD45 med macrophages) as judged by flow cytometry (Denker et al, 2007), which is consistent with our results. CCL2 has been reported to increase BBB permeability in vivo (Stamatovic et al, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, we showed that blood‐derived macrophages began infiltrating the hippocampus in the P9 pups 1 day after HI, but few blood‐derived macrophages infiltrated the hippocampus of the 3mo mice at the same time point. Denker et al reported that the population of blood‐derived macrophages (CD45 high macrophages) in the injured hemisphere 24 hours after HI of P7 rats was 8.8 ± 6.7% and the majority of macrophages were resident microglia (CD45 low and CD45 med macrophages) as judged by flow cytometry (Denker et al, 2007), which is consistent with our results. CCL2 has been reported to increase BBB permeability in vivo (Stamatovic et al, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…suggesting an important role for microglia in ACA-induced neurodegeneration in PND17 rats. Hypoxic-ischemic insults induce proinflammatory cytokine production in both adult and immature brain (Cowell et al, 2002;Denker et al, 2007;Gregersen et al, 2000;Jander et al, 2002). These cytokines can contribute to secondary neurotoxicity or exacerbate ischemic brain damage by recruiting inflammatory cells such as microglia, macrophages, and neutrophils (Kriz, 2006;Minami and Satoh, 2003;Trendelenburg, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a rat model for acute stroke, increased MCP-1, IL-1␤, and CINC-1 were associated with activated microglia prior to neuronal damage (8). Mice infected with the neurovirulent MuLV FrCasE showed increased levels of MIP-1␣ and MIP-1␤ early in the course of disease (3), while mice infected with the neurovirulent polytropic MuLV Fr98 showed increased expression of TNF-␣, TNF-␤, IL-1␣, MIP-1␣, MIP-1␤, MCP-1, IP10, and RANTES (37).…”
Section: Discussionmentioning
confidence: 99%